What drives the Acceptability of Intelligent Speed Assistance (ISA)? - Vlassenroot, Sven; Molin, Eric; Kavadias, Dimokritos; Marchau, Vincent; Brookhuis, Karel; Witlox, Frank (European Journal of Transport and Infrastructure Research, 2011)
To have knowledge about the acceptability of Intelligent Transport systems (ITS) is most beneficial for the development of supported implementation strategies. So far, different theories and methods, also stemming from other domains, have been used to define and conceptualize the notion of acceptability. In a previous paper, we developed a theoretical concept to define acceptability of ISA based on different theories and methods used in ITS & ISA research. In the current paper we aim to find out which predefined indicators are relevant to define the acceptability of ISA. Background factors, contextual issues and ISA-device related factors are used as indicators to predict the level of acceptability. Structural Equation Modelling (SEM) is used to define the direct and indirect effects.